The Influence of Purchasing Strategies on Manufacturing Performance an Empirical Study in Continental Tyre - Othman, Hasbullah; Ibrahim, Irwan; Amer, Afizan; Masrom, Nor Ratna (Innovations in Science and Technology Vol. 4, 2022)
Purpose: The purpose of this study is to examine the importance of purchasing strategies contribution towards manufacturing performance, knowing purchasing function as a key component in organizations. Design/Methodology/Approach: A total of 150 questionnaires were distributed and resulted 110 questionnaires or 73 percent being returned with complete information and used for statistical analysis, to study the significant level of the constructed model among manufacturing firms located in Malaysia which is Continental Tyre. Findings: The results expose that purchasing strategies create a positive significant impact on manufacturing performance which consist of the competitive priorities of the firms in terms of cost, quality, cycle time, delivery speed and dependability, new product introduction time line and last, customization responsiveness performance. Research Limitations/Implications: Manufacturing firms should focus on purchasing strategies, effective negotiation, supplier collaborative relationship and interaction, effective cost management, supply base management and sourcing management as navigators for their merit performance in the current volatile market conditions. Originality/Value: The paper shows that purchasing strategies are appropriate practices for mediating the impact on manufacturing performance in order to stay competitive in the competitive and challenging business environment.